Some Intersections of the Weighted -Spaces - F. Abtahi; H. G. Amini; H. A. Lotfi; A. Rejali (Abstract and Applied Analysis)
Let be a locally compact group an arbitrary family of the weight functions on and . The locally convex space as a subspace of is defined. Also, some sufficient conditions for that space to be a Banach space are provided. Furthermore, for an arbitrary subset of and a positive submultiplicative weight function on , Banach subspace of is introduced. Then some algebraic properties of , as a Banach algebra under convolution product, are investigated.